Cytokine expression during early and late phase of acute Puumala hantavirus infection - Sadeghi, Mahmoud; Eckerle, Isabella; Daniel, Volker; Burkhardt, Ulrich; Opelz, Gerhard; Schnitzler, Paul (BMC immunology, 2011)
Hantaviruses of the family Bunyaviridae are emerging zoonotic pathogens which cause hemorrhagic fever with renal syndrome (HFRS) in the Old World and hantavirus pulmonary syndrome (HPS) in the New World. An immune-mediated pathogenesis is discussed for both syndromes. The aim of our study was to investigate cytokine expression during the course of acute Puumala hantavirus infection.